2001
DOI: 10.1006/anbe.2001.1788
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity facilitates social learning of foraging behaviour in the guppy

Abstract: Previous studies have shown that guppies, Poecilia reticulata, can learn the route to a food source by shoaling with knowledgeable conspecifics, and prefer to shoal with experienced foragers and familiar fish. We tested the hypothesis that guppies would learn more effectively from (1) familiar than unfamiliar demonstrators and (2) well-trained than poorly trained demonstrators. Demonstrator fish were given experience in swimming a route to a food source and then introduced into shoals of untrained observer gup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
199
2
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(211 citation statements)
references
References 25 publications
7
199
2
3
Order By: Relevance
“…However, in many cases, few individuals have pertinent information, such as knowledge about the location of a food source 3,4 , or of a migration route [5][6][7][8][9] . Using a simple model we show how information can be transferred within groups both without signalling and when group members do not know which individuals, if any, have information.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…However, in many cases, few individuals have pertinent information, such as knowledge about the location of a food source 3,4 , or of a migration route [5][6][7][8][9] . Using a simple model we show how information can be transferred within groups both without signalling and when group members do not know which individuals, if any, have information.…”
mentioning
confidence: 99%
“…Although it is likely that some species have a genetically determined propensity to migrate in a general direction 14,15 , or respond to abiotic cues such as thermal gradients that may aid migration 16,17 , it is likely for many species that experienced group members play an important role in guiding those that are less experienced or inexperienced. Relatively few informed individuals within fish schools are known to be able to influence the foraging behaviour of the group 3 and the ability of a school to navigate towards a target 4 . Similarly, very few individuals (approximately 5%) within honeybee swarms can guide the group to a new nest site 7 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, it has been shown that very few individuals within a group may actually possess information on, for example, the direction to a resource (ants, Leptothorax albipennis: Franks et al 2002; honeybees, Apis mellifera: Seeley 2003; golden shiners, Notemigonus crysoleucas (in the laboratory): Reebs 2000; guppies, Poecilia reticulata (in the laboratory) : Reader & Laland 2000;Swaney et al 2001). The simplest situation where such information differences among group members are present could be because of the different spatial positions of individuals.…”
mentioning
confidence: 99%